Accessing Tricyclic Imines Comprising a 2-Azabicyclo[2.2.2]octane Scaffold by Intramolecular Hetero-Diels–Alder Reaction of 4-Alkenyl-Substituted N-Silyl-1,4-dihydropyridines - Rudy, Heinrich-Karl A.; Wanner, Klaus T. (Synthesis, 2019)
Tricyclic imines inheriting a 2-azabicyclo[2.2.2]octane (isoquinuclidine) scaffold were provided with high regioselectivity in moderate to very good yields by a smooth, broadly applicable intramolecular hetero-Diels–Alder reaction of various 4-ω-alkenyl-substituted 1,4-dihydropyridines (DHPs) under trifluoroacetic acid catalysis. The required 4,4-disubstituted 1,4-DHPs were obtained by introduction of ω-alkenyl moieties of varying chain length via diorganomagnesium reagents into the 4-position of diversely 4-substituted pyridines after prior N-activation with triisopropylsilyltriflate.
Keywords: intramolecular hetero-Diels–Alder reaction; 2-azabicyclo[2.2.2]octane; polycycles; 1,4-dihydropyridines; diorganomagnesium reagents; heterocycles